THE HISTORICAL INFLUENCE OF PERSIA ON ISLAM IN SOUTHEAST ASIA AND THE NEED FOR MUSLIM UNITY TODAY - Imtiyaz Yusuf (Media Syari'ah, 2017)
This article will firstly discuss the history of Persian influence in Southeast Asia in relation to Muslim co-existence as well as touch upon the threats to Sunni-Shia unity in Southeast Asia and end with a conclusion. In the section two, this article will discuss the contemporary Sunni-Shia relations of tensions and attempts at reproaching (taqrib) Sunni-Shia reconciliation.